Manutenção elétrica indústrial: retrofit - Lisboa, Gilson da Silva (2022)
This work demosntra the importance of maintenance in the industry is in machine and equipment as well as in building strurura. The correct maintenance can ensure reliability and safety in the production process avoiding accidents with operators, machinery breaks, and losses resulting from sudden stops, industrial globalization becomes increasingly evident the need to ensure that the company can meet goals and deadlines with a quality product; the great challenge of industries today is to understand how to adapt their practices and planning to the demands and tools of now and future, in industrial plants whose projects are more than ten years old maintenance is fundamental for the correct operation of the equipment. It is necessary to bring the technology to the production processes in this way the empreza enhances its productive capacity reduces errors and maximizes gains. In addition to being integrated into the productive routine, technology can (and should) be joined to the industrial maintenance practices of companies; it is a way to minimize the impacts of everyday life, because the wear and tear of the equipment is continuous. The application of new trends such as retrofit (update, modernization) becomes increasingly necessary, aiming at technological monitoring, having an efficient maintenance plan with low cost requires technical planning focused on specific according to the branch of the activity developed. The development of multiple maintenance techniques can bring positive results for the maximum use of equipment and maintaining the conservation of heritage. Also as exemplified in the case study the trend of retrofit (upgrade, modernization), for machines and equipment with more than ten years of manufacture.